Henri de Toulouse-Lautrec - Venezia, Mike.; Toulouse-Lautrec, Henri de, 1864-1901. (Chicago : Childrens Press, 1994)
Describes the life and career of French artist Henri de Toulouse-Lautrec.
Wilson's Children
Elem. School Library Collection
4.6
K-3
Keywords: Toulouse-Lautrec, Henri de, -- 1864-1901 -- Juvenile literature; Toulouse-Lautrec, Henri de, -- 1864-1901.; Artists -- France -- Biography -- Juvenile literature; Artists; Painting, French; Art appreciation; Toulouse-lautrec, Henri de, -- 1864-1901.; Art appreciation; Artists -- Biography; French painting